PENGARUH INVESTMENT OPPORTUNITY SET (IOS) DAN PROFITABILITAS (ROA) TERHADAP KUALITAS LABA PADA PERUSAHAAN SEKTOR BARANG KONSUMEN PRIMER - Alisa Hidayatunisa; Rudiyanto; Taufiqurrohman (Universitas La Tansa Mashiro, 2023)
The purpose of this study is to analyze the Effect of Investment Opportunity Set (IOS) as proxied by Market Value to Book of Assets (MVBVA), and Profitability proxied by Return On Assets (ROA) on Earning Quality in primary consumer goods sector companies listed on the Stock Exchange. Indonesia (IDX) for the period 2018- 2021. The research method used is a quantitative method using secondary data types, the number of samples used is 25 companies with a total of 100 data selected using purposive sampling technique. Analysis of the data used is multiple linear regression analysis and processed using the SPSS version 20 application. The results of the F test, namely the Investment Opportunity Set (IOS), and Profitability (ROA) simultaneously have a simultaneous effect on Earning Quality. The partial test (t test) shows that the Investment Opportunity Set (IOS) has a significant effect on Earning Quality while Profitability (ROA) has a negative effect on Earning Quality. The coefficient of determination shows a value of 14.45 which means that Earnings Quality can be influenced by the Investment Opportunity Set (IOS) and Profitability (ROA) variables. And the remaining 85.6% is influenced by other factors..